Assessing the Efficacy of Methanol Extracts of Ocimum Sanctum Linn. and Ocimum Basilicum Linn. in Diabetic Neuropathy - Khan, Shabeena; Bhanot, Abhishek; Bhandari, Divya Dhawal (Scripta Medica, 2025)
Background/Aim: Our nerves can be impacted by thousands of diseases and ailments, but diabetes-related neuropathy is the name given to the endocrine system issue that results in nerve damage. Herbal plants having antioxidant activity play an important role in managing diabetes and the associated complications. Ocimum sanctum and Ocimum basilicum plants have shown antihyperglycemic as well as neuroprotective activity but the effect of Ocimum sanctum and Ocimum basilicum on diabetic neuropathy (DN) has not been studied so far. So, the given manuscript was aimed to evaluate the effect of both plants by various in vitro biochemical parameters as well as in vivo studies. Methods: The given manuscript describes the effect of methanol extracts of Ocimum sanctum and Ocimum basilicum, in DN induced Swiss albino mice of either sex weighing 25-35 g. Mice were divided into 6 groups viz control (I) receiving citrate buffer, diabetic (II) and test groups (III, IV, V, VI) receiving streptozotocin at a dose of 100 mg/kg to induce DN on 21st day followed by treatment of test groups (III, IV, V, VI) at a dose of 100 mg/kg and 200 mg/kg daily for 14 days, with Ocimum basilicum and Ocimum sanctum, respectively. Results: The results showed that the methanol extracts of Ocimum sanctum and Ocimum basilicum gave significant change in weight variation, tail immersion test and blood glucose in comparison to diabetic control. In brain tissue homogenate measurement of oxidative stress by thiobarbituric acid reactive substance (TBARS), glutathione (GSH) and serum nitrite level, the methanol extract of both plants produced significant change when compared to diabetic control. Conclusion: This study underscores the promising role of herbal adjuncts in addressing the complexities of diabetic neuropathy and warrants continued investigation into their clinical utility.